A Standardized Protocol for Stereotaxic Intrahippocampal Administration of Kainic Acid Combined with Electroencephalographic Seizure Monitoring in Mice - Bielefeld, Pascal; Sierra, Amanda; Encinas, Juan M.; Maletic-Savatic, Mirjana; Anderson, Anne; Fitzsimons, Carlos P. (Frontiers in Neuroscience, 2017)
Lack of scientific reproducibility is a growing concern and weak experimental practices may contribute to irreproducibility. Here, we describe an optimized and versatile protocol for stereotaxic intrahippocampal administration of Kainic Acid (KA) in mice with a C57Bl6 background. In this protocol, KA administration is combined with in vivo recording of neuronal activity with wired and wireless setups. Following our protocol, KA administration results in a robust dose-dependent induction of low-level epileptiform activity or Status Epilepticus (SE) and induces previously characterized hallmarks of seizure-associated pathology. The procedure consists of 3 main steps: craniotomy, stereotaxic administration of KA, and placement of recording electrodes in intrahippocampal and subdural locations. This protocol offers extended possibilities compared to the systemic administration of KA, as it allows the researcher to accurately regulate the local dose of KA and resulting seizure activity, and permits the use and study of convulsive and nonconvulsive KA doses, resulting in higher reproducibility and lower inter-individual variability and mortality rates. Caution should be taken when translating this procedure to different strains of mice as inter-strain sensitivity to KA has been described before. The procedure can be performed in approximately 1 hour by a trained researcher, while intrahippocampal administration of KA without placing recording electrodes can be done in 25 minutes, and can be easily adapted to the titrated intrahippocampal administration of other drugs.